2016
DOI: 10.1093/nar/gkw590
|View full text |Cite
|
Sign up to set email alerts
|

The zinc fingers of YY1 bind single-stranded RNA with low sequence specificity

Abstract: Classical zinc fingers (ZFs) are traditionally considered to act as sequence-specific DNA-binding domains. More recently, classical ZFs have been recognised as potential RNA-binding modules, raising the intriguing possibility that classical-ZF transcription factors are involved in post-transcriptional gene regulation via direct RNA binding. To date, however, only one classical ZF-RNA complex, that involving TFIIIA, has been structurally characterised. Yin Yang-1 (YY1) is a multi-functional transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 64 publications
(88 reference statements)
2
32
0
Order By: Relevance
“…Full-length hYY1 protein rescued Xist RNA localization to the Xi, with nearly identical levels of Type I/II Xist RNA patterns as wildtype B cells ( Fig 6B and 6C ). The N-terminal domain (NTD) of hYY1 (1–200 amino acids) contains the transcriptional activation domain and interacts with histone acetyltransferases and histone deacetylases [ 54 , 55 ], as well as RNA binding activity that is independent of the zinc finger domain [ 26 ]. However, we found that expression of the 1–200 amino acid protein did not rescue the Xist RNA localization defect ( Fig 6B and 6C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-length hYY1 protein rescued Xist RNA localization to the Xi, with nearly identical levels of Type I/II Xist RNA patterns as wildtype B cells ( Fig 6B and 6C ). The N-terminal domain (NTD) of hYY1 (1–200 amino acids) contains the transcriptional activation domain and interacts with histone acetyltransferases and histone deacetylases [ 54 , 55 ], as well as RNA binding activity that is independent of the zinc finger domain [ 26 ]. However, we found that expression of the 1–200 amino acid protein did not rescue the Xist RNA localization defect ( Fig 6B and 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…The Xist promoter region contains YY1 binding sites and YY1 enhances Xist expression during XCI initiation and maintenance in mammalian cells [ 24 ]. The YY1 protein can also bind RNA [ 25 , 26 ], and the Repeat C region of Xist contains three YY1 binding sites required for tethering Xist RNA to the chromatin of the Xi in post-XCI somatic cells [ 27 ]. YY1 mediates the long-distance DNA interactions required for V(D)J recombination of the immunoglobulin loci and for class switch recombination, and B cell specific YY1 deletion arrests B cell development at the pro-B cell stage [ 28 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies by Wai et al . using systematic evolution of ligands by exponential enrichment (SELEX) and related approaches have determined that the zinc fingers of YY1 bind with low sequence‐specificity to single‐stranded RNA in a manner distinct from its binding to DNA . Recent work has also found that YY1 is tyrosine‐phosphorylated by Src family kinases.…”
Section: Discussionmentioning
confidence: 99%
“…A lncRNA transcribed from the YY1 gene promoter (linc-YY1) interacts with YY1 through its middle domain to evict YY1-PRC2 from target promoters, thus activating gene expression in trans ( 124 ). A recent SELEX (systematic evolution of ligands by exponential enrichment) study found that YY1 interacts with RNA with low sequence specificity ( 125 ), and the lack of RNA sequence specificity has been commonly observed among chromatin binders more generally. The biochemical and structure nature of the protein-RNA interaction may determine the inhibition or activation mechanism.…”
Section: Transcription Factorsmentioning
confidence: 99%